PENGARUH HARGA DAN LOKASI TERHADAP KEPUTUSAN KONSUMEN BELANJA DI ATHAMART SWALAYAN BUKIT LAMA PALEMBANG (Studi Kasus) - Alhusori -; Yusnizal Firdaus (Jurnal Media Wahana Ekonomika, 2016)
The rapid development of the emergence of a variety of Minimarket airport selling various household needs, both located within the urban environment has penetrated even at the village level, making trade competition becomes more intense, Athamart located at Jalan Sultan Mansyur Bukit Lama Palembang, is one of the Mini Market is able to compete with other competitors with a similar business, judging from the trend of return and the number of visitors enough to give a good future in the future, it is seen from the reception Athamart reached Rp. 35,000,000, - per day with a visitor capacity of approximately 300 people, the results of the analysis of multiple trend equation as follows: Y = 5.7 + 0389 (X1) + 0706 (X2), of the analysis obtained if X1 and X2 are the same price and location factors premises 0, the sales volume of at least 5.7 units or equivalent to Rp. 570.000, - per day, if there is an increase of one unit variable X1, the obtained increase of Rp. 38.900, - whereas when they both moved up one unit then it will be obtained an increase of Rp. 570,000 + Rp. 38,900 + Rp. 70 600 = Rp. 679 500, - thus the price factor and the location will show a positive trend.Keywords : Purchasing, Decision, Product, Price, Location.